Learning the Science of Tajwid and Tahsin of the Koran in Tegalwirangrong Village, Kertasemaya District, Indramayu Regency - Ginal Leby; Ibnu Rusydi; Ibnudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The aim of this program is for children to understand the science of recitation and Tahsin of the Koran. While the benefits of this program are that children are able to apply the knowledge of recitation when reading the Qur'an so that there are no mistakes in reading it. The approach used in carrying out this supporting program is the lecture, demonstration and question and answer method. The results of learning Tajwid and Tahsin Al-Quran make children who take part in the learning able to understand what recitation is, starting from the law of Nun Mati or Tanwin to understanding and how to read Mad, so that children can implement the material above when reading Al-Quran with good and right.